From Circuit Simulation to Circuit Verification: An Internal + Boundary Scan-based Solution - Alves, Gustavo R. (2017)
Matching the results obtained from circuit simulation with those extracted from circuit functioning is a common stage of the final verification process. Many current verification techniques use the I/O vectors produced during functional and / or timing simulation, for creating the test vectors to be applied / compared against the circuit responses. Techniques that are more complete include extracting the values of internal sequential nodes and comparing these using internal scans. This paper describes such a solution for verifying digital designs implemented in currently commercial available CPLDs. The test program is automatically generated from information that encompasses the design & development phase, namely: the file containing the results from simulation, the BSDL file, an internal scan chain description file, and one file containing the user options.